Cluster analysis of symptoms and health seeking behaviour differentiates subgroups of patients with severe irritable bowel syndrome. Issue 11 (21st October 2003) - Guthrie, E; Creed, F; Fernandes, L; Ratcliffe, J; Van der Jagt, J; Martin, J; Howlett, S; Read, N; Barlow, J; Thompson, D; Tomenson, B
Abstract : Background: Irritable bowel syndrome (IBS) is a heterogeneous condition which is diagnosed according to specific bowel symptom clusters. The aim of the present study was to identify subgroups of IBS subjects using measures of rectal sensitivity and psychological symptoms, in addition to bowel symptoms. Such groupings, which cross conventional diagnostic approaches, may provide greater understanding of the pathogenesis of the condition and its treatment. Method: A K means cluster analysis was used to group 107 clinic patients with IBS according to physiological, physical, and psychological parameters. All patients had severe IBS and had failed to respond to usual medical treatment. Twenty nine patients had diarrhoea predominant IBS, 26 constipation predominant, and 52 had an alternating bowel habit. Results: The clusters were most clearly delineated by two variables: "rectal perceptual threshold (volume)" and "number of doctor visits". Three subgroups were formed. Group I comprised patients with low distension thresholds and high rates of psychiatric morbidity, doctor consultations, interpersonal problems, and sexual abuse. Group II also had low distension thresholds but low rates of childhood abuse and moderate levels of psychiatric disorders. Group III had high distension thresholds, constipation or alternating IBS, and low rates of medical consultations and sexual abuse. Conclusion: The marked differences across the three groups suggest that each may have a different pathogenesis and respond to different treatment approaches. Inclusion of psychosocial factors in the analysis enabled more clinically meaningful groups to be identified than those traditionally determined by bowel symptoms alone or rectal threshold.